2013
DOI: 10.1523/jneurosci.4852-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral TGF-β1 Signaling Is a Critical Event in Bone Cancer-Induced Hyperalgesia in Rodents

Abstract: Pain is the most common symptom of bone cancer. TGF-␤, a major bone-derived growth factor, is largely released by osteoclast bone resorption during the progression of bone cancer and contributes to proliferation, angiogenesis, immunosuppression, invasion, and metastasis. Here, we further show that TGF-␤1 is critical for bone cancer-induced pain sensitization. We found that, after the progression of bone cancer, TGF-␤1 was highly expressed in tumor-bearing bone, and the expression of its receptors, TGF␤RI and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 45 publications
(3 reference statements)
2
62
0
Order By: Relevance
“…Emerging evidence has highlighted that CXCL12/ CXCR4 signaling is responsible for pleiotropic aspects of metastatic cancer progression including homing, survival, proliferation, and angiogenesis in bone marrow microenvironment (Sun et al 2010;Shi et al 2014). It is well known that, after metastasized to bone, the secondary tumors in the advanced stage subsequently result in BCP (Duan et al 2012;Xu et al 2013). Interestingly, we further found that, in a rat model of tibia metastasis, CXCL12/CXCR4 signaling in the spinal dorsal horn was also responsible for BCP development, in addition to its oncogenic roles in tumor-burdened bone.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Emerging evidence has highlighted that CXCL12/ CXCR4 signaling is responsible for pleiotropic aspects of metastatic cancer progression including homing, survival, proliferation, and angiogenesis in bone marrow microenvironment (Sun et al 2010;Shi et al 2014). It is well known that, after metastasized to bone, the secondary tumors in the advanced stage subsequently result in BCP (Duan et al 2012;Xu et al 2013). Interestingly, we further found that, in a rat model of tibia metastasis, CXCL12/CXCR4 signaling in the spinal dorsal horn was also responsible for BCP development, in addition to its oncogenic roles in tumor-burdened bone.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…signaling sensitizes TRPV1 in primary sensory neurons. [14][15][16] ] i increase. Thus, another possibility mediating the acute effects of TGF-β1 is that calcium released from intracellular calcium pools as a second message opens one or more non-selective cation channels in direct or indirect ways, thus resulting in robust depolarization and discharges.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence suggests that TGF-β1 has protective effects against neuropathic pain in the central nervous system, 11,12 while in peripheral nervous system, TGF-β1 is recently reported as an algogenic substance that contributes to peripheral sensitization by downregulation of the KCNA4 gene, 13 or activation of cyclin-dependent kinase-transient receptor potential vanilloid type 1 (Cdk5-TRPV1) signaling 14,15 and transforming growth factor β activated kinase 1 (TAK1)/protein kinase C (PKC)-TRPV1 signaling. 16 As mentioned in those studies, [13][14][15][16] TGF-β1 is a complex modulator of sensory neuronal function, and its signaling pathway in the induction and development of pancreatic pain in rats with chronic pancreatitis was not fully understood. Therefore, the roles of TGF-β1 and its receptors were re-explored in the setting of chronic pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…63 Attempts to develop or identify antagonists devoid of temperature effects have not been successful. In this context, it is noted that recent studies have shown that the expression and activity of TRPV1 on the DRG sensory neurons are upregulated by TGF-b1 64 and IGF-1. 65 Further, these studies showed that inhibition of TGF-b or IGF receptor signaling reduced CABP through suppression of TRPV1 activation.…”
Section: Cancer-colonized Bonementioning
confidence: 99%